Simplified method for estimating vertical stress-settlement responses of piled embankments on soft soils. (March 2020) - Rui, Rui; Han, Jie; Zhang, Lei; Zhai, Yuxin; Cheng, Zhi; Chen, Cheng
Abstract: Soil arching development patterns of piled embankment have been comprehensively investigated by performing multi-trapdoor tests in many previous studies. However, the application of these findings is inevitably limited as the subsoil-pile system under the embankment is generally not explicitly taken into account. In this study, an analytical method was employed to evaluate the compressibility of the subsoil-pile system. The compressibility analysis results were used together with the analytical models for soil arching development obtained from multi-trapdoor tests to estimate the vertical stress-settlement response of the subsoil-pile-embankment system. A parametric study was conducted to investigate the effect of the following influence factors: friction angle of embankment fill, embankment height, coefficient of skin friction, pile spacing, pile cap width, and pile to subsoil modulus ratio on the vertical stress-settlement response. Based on the parametric study, correlations were developed between the influence factors and the vertical stress-settlement responses of the subsoil-pile-embankment system. The developed method was favorably examined by a set of field test results in the literature.